EU Issue Voting: Asset or Liability?: How European Integration Affects Parties’ Electoral Fortunes - de Vries, Catherine (Sage Journals, 2010)
This study develops and tests arguments about how political parties’ electoral fortunes in national elections are influenced by voters’ preferences regarding the European Union (EU). To date, there is increasing evidence demonstrating the impact of EU issues on vote choice in national elections — a process commonly referred to as EU issue voting. Yet little is known about which parties actually gain or lose as a result of EU issue voting. Using a two-step hierarchical estimation procedure, I first estimate an individual-level model of vote choice estimating the impact of EU preferences for individual parties. The first stage of the analysis reveals that the extent of EU issue voting varies substantially among political parties. In the second stage, I utilize party characteristics to account for this variation across parties by using an estimated dependent variable model. The analysis demonstrates that the inter-party variation in EU issue voting is largely a function of two factors: parties’ intrinsic positioning regarding the EU and strategic considerations. The empirical analysis employs data from UK, Danish, Dutch and German elections between 1992 and 2002
Keywords: 59 Ciencia Política::5905 Vida política::5905.01 Elecciones; ODS 16 - Paz, justicia e instituciones sólidas